Penguatan Pola Asuh Orang Tua bagi Perkembangan Kognitif Anak di Desa Guci Kecamatan Sirampog - Jamiah Jamiah (Institut Agama Islam Negeri Purwokerto, 2021)
The family is the first environment in the education of a child to adapt well according to his age and maturity. In the family, parents have a big role in influencing the development of children's cognitive intelligence. Parenting patterns in early childhood include the provision of physical stimulation, mental stimulation, emotional stimulation, moral stimulation and also social stimulation that will encourage optimal child development. Good parenting will affect the development of children well as well as bad parenting will hinder the development of children. Parenting patterns mean the habits of parents, fathers and mothers in leading, nurturing and guiding children. Nurturing in the sense of keeping by caring for and educating him. Guiding by helping, training, accompanying and so on. The quality and intensity of parenting styles vary in influencing attitudes and directing children's behavior. Therefore, the author will discuss issues related to the relationship between parenting patterns and the development of children's cognitive intelligence, such as the definition of parenting patterns, cognitive intelligence and children. And also discusses the factors that influence the development of children's cognitive intelligence, such as parents' educational background, economy, early marriage, work and environment.The purpose of this study was to determine how big the relationship between parenting patterns and the development of children's intelligence. This research uses descriptive qualitative method. Data collection techniques are observation and interviews. The results showed that parenting greatly influences the development of children's cognitive intelligence in Guci Village, Sirampog District, and good parenting is also influenced by many factors. Keywords: parenting, cognitive intelligenc, children. Keluarga merupakan lingkungan pertama dalam pendidikan seorang anak untuk memyesuaikan diri dengan baik sesuai usia dan kematangannya. Didalam keluarga orang tua memiliki peran besar dalam memberikan pengaruh pada perkembangan kecerdasan kognitif anak. Pola asuh orang tua pada anak usia dini mencakup pemberian rangsangan fisik, rangsangan mental, rangsangan emosional, rangsangan moral dan juga rangsangan social yang akan mendorong tumbuh kembang anak secara optimal. Pola asuh yang baik akan mempengaruhi perkembangan anak dengan baik pula begitu juga pola asuh yang buruk akan menghambat perkembangan anak. Pola assuh orang tua berarti kebiasaan orang tua, ayah dan ibu dalam memimpin, mengasuh dan membimbing anak. Mengasuh dalam arti menjaga dengan cara merawat dan mendidiknya. Membimbing dengan cara membantu, melatih, mendampingi dan sebagainya. Kualitas dan intensitas pola asuh orang tua bervariasi dalam mempengaruhi sikap dan mengarahkan perilaku anak. Karena itu penulis akan membahas masalah-masalah yang berkaitan dengan hubungan pola asuh orang tua terhadap perkembangan kecerdasan kognitif anak, seperti definisi pola asuh orang tua, kecerdasan kognitif dan anak serta faktor-faktor yang mempengaruhi perkembangan kecerdasan kognitif anak, seperti latar belakang pendidikan orang tua, ekonomi, pernikahan dini, pekerjaan dan lingkungan.Tujuan penelitian ini untuk mengetahui seberapa besar hubungan pola asuh orang tua terhadap perkembangan kecerdasan anak. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik pengumpulan data yaitu observassi dan wawancara. Hasil penelitian menunjukan bahwa pola asuh orang tua sangat mempengaruhi perkembangan kecerdasan kognitif anak di Desa Guci Kecamatan Sirampog, dan pola asuh yang baik juga dipengaruhi banyak faktor. Kata kunci: Pola asuh orang tua, kecerdasan kognitif, anak